Person-centered support for patients with a pituitary tumor following surgery - Sofie Jakobsson; Oskar Ragnarsson; Tobias Hallén; David Krabbe; Ann-Charlotte Olofsson; Daniel S Olsson; Penelope Trimpou; Thomas Skoglund; Gudmundur Johannsson (Endocrine Connections)
Objectives: To evaluate whether a person-centered care practice following surgery for pituitary tumors increased psychological well-being. Secondary aims were to study whether person-centered care would lead to better health status, less fatigue and better self-efficacy. Design and methods: This study is a prospective, single-center study using a quasi-experimental design to evaluate the effect of a 12-month person-centered practice by means of a name-given nurse care manager, an interdisciplinary team and peer support against usual care. All patients (≥18 years) with a benign pituitary tumor and planned for endoscopic transsphenoidal surgery were consecutively invited to participate. Psychological well-being, self-reported health, fatigue and self-efficacy were assessed before surgery, at discharge and 3–6 and 12 months after surgery. Results: In total, 86 patients in the intervention group and 68 patients in the control group were included. Psychological well-being improved 12 months following surgery in both groups to comparable levels. The intervention group had a greater improvement in anxiety compared to the control group (P = 0.02). No differences were seen between groups in self-reported health status, fatigue or self-efficacy. Patients in the intervention group with other types of pituitary tumors than non-functioning pituitary adenomas showed a greater improvement in psychological well-being than in the control group. Conclusion: Our intervention did not result in major advantages in terms of health or psychological well-being. The study does, however, suggest that the intervention may reduce anxiety 12 months after surgery and that certain subgroups of patients may benefit more from a structured person-centered practice following pituitary surgery.